Pengaruh Motivasi dan Minat Belajar Terhadap Kemampuan Pemecahan Masalah Matematis: Penelitian - Aurelia Febriyanti; Ettie Rukmigarsari; Tri Candra Wulandari (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the combined effect of learning motivation and learning interest on students' problem-solving abilities, to determine the effect of learning motivation on students' problem-solving abilities, and to determine the effect of learning interest on students' problem-solving abilities. This study was conducted at SMP Negeri 19 Kota Malang. The approach used in this study was a quantitative approach with an ex-post facto type, with the research population consisting of all eighth-grade students at SMPN 19 Kota Malang, totaling 340 students. The researcher used 28 students as the research sample, selected using cluster random sampling by drawing lots for grade 8A to 8J and randomly selecting two class. The instruments used in this study were tests and questionnaires. The questionnaire was used to obtain data on motivation and interest in learning. The scores obtained from the learning motivation and interest questionnaire were ordinal data, which were then transformed using the Successive Interval Method (MSI) into interval data. Data analysis techniques used multiple linear regression analysis with the backward method. The research results indicate that there is no combined effect of motivation and interest in learning on students' problem-solving abilities, no effect of motivation in learning on students' problem-solving abilities, and an effect of interest in learning on students' problem-solving abilities.